Quantifying the Effect of Temporomandibular Joint Intra-Articular Steroid Injection on Synovial Enhancement in Juvenile Idiopathic Arthritis - Resnick, Cory M.; Vakilian, Pouya M.; Kaban, Leonard B.; Peacock, Zachary S. (Journal of oral and maxillofacial surgery, 2016)
To quantify the effect of intra-articular steroid injections (IASIs) on temporomandibular joint (TMJ) synovitis in children with juvenile idiopathic arthritis (JIA) using gadolinium-enhanced magnetic resonance imaging (MRI). The present study was a retrospective study of children with JIA who had undergone TMJ IASIs at Boston Children's Hospital. The patients were included if they had undergone contrast-enhanced MRI both before and after IASI and if the pre-IASI MRI had demonstrated synovitis (enhancement ratio [ER] >1.55). Patients with TMJ pathology or pain unrelated to JIA or a history of facial trauma were excluded. The predictor variables were age, gender, JIA subtype, exposure to medications for arthritis, and a family history of autoimmune disease. The primary outcome variable was the ER. Additional outcome variables included patient-reported pain and the maximal incisal opening (MIO). Twenty-nine subjects (83% female) with a total of 50 injected TMJs were included. The average age at JIA diagnosis and at IASI was 6.8 ± 1.7 years and 12.1 ± 1.9 years, respectively. The mean follow-up period was 22.9 ± 4.3 months (range 5 to 48). The ER decreased in all injected joints, with a mean reduction of 1.05 ± 1.01 (P < .001). The post-IASI ER was less than the normal threshold (1.55) in 18% of the injected TMJs. IASI was associated with an elimination of pain in 89% of the subjects (P < .001) and in augmentation of the MIO by 5.8 ± 2.6 mm (P < .001). In children with JIA and TMJ synovitis, TMJ IASI was associated with a reduction in synovial enhancement, decreased pain, and an increased MIO. Only 18% of injected joints, however, experienced complete resolution of synovitis. These results support the use of IASI in the management of the pain and dysfunction associated with TMJ synovitis. Further study is required to determine the efficacy of IASI in limiting inflammation and future joint destruction.